The effect of Ganqichengpi syndrome diarrhea and Tongxie Yaofang intervention on the intestinal mucosal microbiota and neurochemical substances - Long, Chengxing; Liu, Yan; Yu, Zizhen; Liu, Jialin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo explore the regulatory effect of Tongxie Yaofang prescription on intestinal mucosal microbiota in mice with Ganqichengpi syndrome diarrhea by 16S rRNA high-throughput sequencing.MethodsGanqichengpi syndrome diarrhea model was replicated via the Folium senna extract combined with restraint and tail pinch stress. After the model was successfully replicated, the treatment was carried out with the Tongxie Yaofang. Once the modeling and treatment experiments were completed, the levels of 5-hydroxytryptamine (5-HT), vasoactive intestinal peptide (VIP), and brain-derived neurotrophic factor (BDNF) in serum were determined by enzyme-linked immunosorbent assay. The pathological changes of liver tissues were detected by HE staining technology, and the characteristics of intestinal mucosal microbiota were analyzed by 16S rRNA gene high-throughput sequencing technology.ResultsThe results showed that modeling significantly increased the levels of VIP and BDNF, and significantly decreased the level of 5-HT. After the intervention of Tongxie Yaofang, the level of BDNF remained high, but it had no significant effect on 5-HT and VIP. The results of the relative abundance of microbiota showed that Bacillota was the main microbiota in the intestinal mucosa and occupied an absolute dominant position. At the phylum level, the modeling of Ganqichengpi syndrome diarrhea increased the relative abundance of Bacillota, significantly raising the ratio of Bacillota to Bacteroides. After treatment with Tongxie Yaofang, they basically returned to the normal group level. At the genus level, Clostridiaceae Candidatus, Lactobacillus, and Streptococcus were the top three dominant genera. Modeling reduced the relative abundance of Lactobacillus and increased the relative abundance of Clostridiaceae Candidatus. After the treatment with Tongxie Yaofang, the relative abundance of Lactobacillus increased, while Clostridiaceae Candidatus and Streptococcus decreased. The LEfSe analysis results indicated that Lactobacillus was the biomarker genus in the normal group in the modeling experiments. Under the condition of an LDA threshold of 4, no biomarker genera were found in each group in the treatment experiment, but the relative abundance of Lactobacillus significantly increased in the treatment group.ConclusionThe therapeutic effect of Tongxie Yaofang was achieved by altering the abundance of Lactobacillus, the dominant microbiota in the intestinal mucosa, through three possible pathways.